Study on Morphological Evolution of Ag-nanostructured Films Prepared by Mass-selected Clusters - Pintu Barman; Anindita Deka; Satyaranjan Bhattacharyya (Newest Updates in Physical Science Research Vol. 12, 2021)
Fabrication of metal nanoclusters via gas phase synthesis method and their deposition on a solid surface has numerous importances as far as the application is concerned. The size of the deposited nanostructure can influence various properties of a thin film which led us to carry out the study of morphological aspects of the films that have been prepared by the mass- or size-selected silver nanoclusters on Si substrates. The Ag-nanoclusters films are produced by using a gas aggregation type magnetron-based nanocluster source and the size-selection is done by a Quadrupole Mass Filter (QMF) attached with the cluster source. The film deposition is carried out at varied cluster beam current for constant deposition time for the cluster size of about 4 nm diameter. The morphology of the films is investigated by atomic force microscopy (AFM) and scanning electron microscopy (SEM). From the observations, it is found that initially the nanostructured film is mono-dispersed for a lower cluster ion current while for higher ion current mound-like structures appear. The effects of surface diffusion and agglomerations of deposited clusters are discussed for the formation of mound-like structures. Structural and composition studies show the elemental purity of the films under investigation.